The relationship between exchange rate, quantity exported of cashew nut and price received by producers in Rio Grande do Norte state, Brazil - da Costa, José Marcione; de Lima Guedes, Maria Josiane; Melo, André de Souza (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This paper seeks to examine the relationship between the exchange rate, the quantity of exported cashew nuts and the price received by producers in the Brazilian state of Rio Grande do Norte from January 2010 to June 2016. The study is justified by the fact the production chain of cashew nut almonds has a great socioeconomic importance in the state in question. To achieve the purpose of the study, Granger causality tests and the econometric model of autoregressive vectors (VAR) were used. The analysis results demonstrated that exports react to exchange rate changes to a greater extent only in the short term. Moreover, the series were shown to have basically autoregressive structures.